4D structural biology: the 9th Murnau Conference on structural biology : meeting report - Hennig, Janosch; Batista Paulino, Cristina (Structure, 2025)
The data presented at the 9th International Murnau Conference on September 18-21, 2024, the largest recurring structural biology meeting in Central Europe, illustrated the thriving state of the structural biology community. This is largely attributed to the ground-breaking developments over the last decade, which were intensely discussed during the meeting.
Gesehen am 31.07.2025